2022
DOI: 10.1136/ard-2022-222605
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated B cells contribute to the pathogenesis of rheumatoid arthritis by inducing activation of fibroblast-like synoviocytes via TNF-α-mediated ERK1/2 and JAK-STAT1 pathways

Abstract: ObjectivesAge-associated B cells (ABCs) are a recently identified B cell subset, whose expansion has been increasingly linked to the pathogenesis of autoimmune disorders. This study aimed to investigate whether ABCs are involved in the pathogenesis and underlying mechanisms of rheumatoid arthritis (RA).MethodsABCs were assessed in collagen-induced arthritis (CIA) mice and patients with RA using flow cytometry. Transcriptomic features of RA ABCs were explored using RNA-seq. Primary fibroblast-like synoviocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 47 publications
5
53
0
Order By: Relevance
“…Recently, by combining mass cytometry and single-cell RNA sequencing analyses, Zhang et al (29) revealed that ABCs were expanded in the synovium of RA patients, suggesting a potential role of ABCs in inflammatory arthritis. Consistently, a recent work in our lab has confirmed the expansion of ABCs both in the peripheral blood and in the synovial tissue of RA patients (30). Our findings demonstrated a distinct transcriptomic feature of RA ABCs, which may impact their ability to migrate into the inflammatory joints, where they induce FLS to an aggressive phenotype and perpetuate synovitis development (30).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recently, by combining mass cytometry and single-cell RNA sequencing analyses, Zhang et al (29) revealed that ABCs were expanded in the synovium of RA patients, suggesting a potential role of ABCs in inflammatory arthritis. Consistently, a recent work in our lab has confirmed the expansion of ABCs both in the peripheral blood and in the synovial tissue of RA patients (30). Our findings demonstrated a distinct transcriptomic feature of RA ABCs, which may impact their ability to migrate into the inflammatory joints, where they induce FLS to an aggressive phenotype and perpetuate synovitis development (30).…”
Section: Introductionsupporting
confidence: 90%
“…Consistently, a recent work in our lab has confirmed the expansion of ABCs both in the peripheral blood and in the synovial tissue of RA patients (30). Our findings demonstrated a distinct transcriptomic feature of RA ABCs, which may impact their ability to migrate into the inflammatory joints, where they induce FLS to an aggressive phenotype and perpetuate synovitis development (30).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by synovitis, progressive articular cartilage erosion, and bone destruction, which is regulated by a complex pathological process involving multiple inflammatory cells. , Nowadays, pathological research has revealed that fibroblast-like synovial (FLS) cells are one of the critical effector cells in RA, and their hyperproliferation and infiltration play a key role in the pathogenesis of RA. , Once RA happens, the two- to three-layer synovial lining would be converted to rheumatoid and pannus-like, which is a hyperplastic structure with a greater amount of stimulated FLS cells and macrophages that stretches into the articular interior, connects to the cartilage surface, and infiltrates and decomposes the cartilage matrix leading to bone loss and joint dysfunction. Recently, many research reports demonstrate that the activation of FLS cells and subsequent joint injury are closely related to the changes of intracellular energy metabolism. , In RA activated FLS (RA-FLS) cells, the balance of the glucose metabolism is disturbed, which is reflected as the proportion of the glycolysis pathway being obviously higher than that of the oxidative phosphorylation pathway. With the rise of glycolysis and acid resistance, RA-FLS cells are especially sensitive to glucose and highly dependent on glycolysis and have a tenacious vitality advantage, which is the main factor for the rapid proliferation and invasion of inflammatory synovium .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nowadays, pathological research has revealed that fibroblastlike synovial (FLS) cells are one of the critical effector cells in RA, and their hyperproliferation and infiltration play a key role in the pathogenesis of RA. 3,4 Once RA happens, the two-to three-layer synovial lining would be converted to rheumatoid and pannus-like, which is a hyperplastic structure with a greater amount of stimulated FLS cells and macrophages that stretches into the articular interior, connects to the cartilage surface, and infiltrates and decomposes the cartilage matrix leading to bone loss and joint dysfunction. 5−7 Recently, many research reports demonstrate that the activation of FLS cells and subsequent joint injury are closely related to the changes of intracellular energy metabolism.…”
Section: Introductionmentioning
confidence: 99%